Improved Field-Oriented Control for PWM Multi-level inverter-Fed Induction Motor Drives - Daniel Legrand Mon Nzongo; Emilienne Leugoue; Jianhua Zhang; Gabriel Ekemb (Institute of Advanced Engineering and Science, 2018)
This paper proposes a new approach to ensure the torque decoupled to the rotor flux of an induction machine based on the Field Oriented Control (FOC). The suggested method consists of inserting into the conventional d-q synchronous current controller, coupling terms of motor and multi-level inverter models. Making, the dynamic response of stator current components decoupled as well as the rotor flux and torque. In this paper, the mathematic model of an induction motor and multi-level inverter are first derived. Then, the synchronous current controller and modulation strategy for high power inverters are investigated. Finally, the validation through implementation and simulation of a 4.16 kV electric drive with MATLAB/Simulink and SimPowerSystems is performed. The model simulated in this paper includes an induction motor, nine-level cascaded H-bridge inverter and a carrier based space vector pulse-width-modulation.The results of the simulations of each method has been recorded and the comparison results reveal that the proposed method effectively maintains the rotor flux decoupled to the torque.